Analisis Sistematisasi Data Pokok Pendidikan di Yayasan Harapan Umat Karawang (Current Research in Education: Conference Series Journal, 2023)
The Basic Education Data Application has become a mandatory application for all schools in Indonesia. Every year the Basic Education Data app is updated for the improvement of its users. Information system analysis of Basic Education Data was carried out at the Harapan Ummah Foundation School in Karawang with the aim of knowing the details of the systematization analysis, the data flow that runs in it, various other applications that have implications for Basic Education. Data applications (such as Student Verval, Educator Verval and Education Personnel, and verification of mobile phones), important functional requirements, especially the user interface and user experience, as well as obstacles to managing Basic Data Education in schools. Application analysis as information that can be a further development of the application. This research method is qualitative. Data was collected by interviewing the school operator Yayasan Komunitas Harapan. The hope of this research is that the authors can obtain information that can give birth to innovations in the application of Basic Education Data and become a means to convey recommendations to stakeholders. The conclusion is that the Dapodik application needs to make improvements to features that are not too important and the server is down.